MODEL PEMBELAJARAN ISU-ISU KONTROVERSIAL DALAM PEMBELAJARAN SEJARAH - Jenny K. Matitaputy (Sosio-Didaktika: Social Science Education Journal, 2016)
AbstractLearning history has a meaning that is very important in shaping the characteristics of the community and the nation. History as part of a social science that has extensive learning resources, both in the classroom or outside the classroom. This article seeks to provide an overview of the development of the learning model of controversial issues in the teaching of history. Through the development of learning models of controversial issues are expected to study history will be able to train and develop students’ critical thinking skills and to train and develop a tolerant attitude while dealing with different situations and conditions (pros and cons). Through learning model of controversial issues, the teaching of history is no longer monotonous and boring, but dynamic and exciting learning.Abstrak Pembelajaran sejarah mengandung makna yang sangat penting dalam membentuk karakteristik masyarakat dan bangsa. Sejarah sebagai bagian dari IPS memiliki sumber belajar yang luas, baik di dalam kelas ataupun di luar kelas. Artikel ini berusaha memberikan gambaran tentang pengembangan model pembelajaran isu-isu kontroversial dalam pembelajaran sejarah. Melalui pengembangan model pembelajaran isu-isu kontroversial diharapkan pembelajaran sejarah akan mampu melatih dan mengembangkan kemampuan berpikir kritis siswa serta melatih dan mengembangan sikap toleran saat berhadapan dengan situasi dan kondisi yang berbeda (pro dan kontra). Melalui model pembelajaran isu-isu kontroversial, pembelajaran sejarah bukan lagi bersifat monoton dan membosankan, melainkan pembelajaran yang dinamis dan menarik.Pengutipan: Matitaputty, J. K. (2016). Model Pembelajaran Isu-isu Kontroversial dalam Pembelajaran Sejarah. SOSIO DIDAKTIKA: Social Science Education Journal, 3(2), 2016, 184-192. doi:10.15408/sd.v3i2.4365.Permalink/DOI: http://dx.doi.org/10.15408/sd.v3i2.4365